Peran Guru PAK Dalam Mengisi Kekosongan Spiritual Anak Dari Keluarga Broken Home - Yakob Mailani; Mozes Lawalata (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Broken home families, which are characterized by the breakdown of parental relationships, can have a negative impact on children's development, including spiritual emptiness. In this context, the role of Christian religious teachers is important in filling the spiritual void of children from broken homes. This article aims to investigate the role of Christian religious teachers in filling the spiritual void of children from broken home families and the strategies that can be used to achieve this. In the introduction, the article explains the meaning of a broken home family and identifies its impact on the child's spiritual emptiness. Then, the article continues by discussing the role of Christian religious teachers in filling the spiritual void in children. Christian religious teachers not only serve as teachers, but also as a source of spiritual support and example for children. Furthermore, the article reviews strategies and approaches that can be used by Christian religious teachers in filling the spiritual void of children from broken home families. Relevant and interactive teaching methods, building emotional relationships with children, and efforts to cultivate spiritual awareness through reflection and meditation are some of the recommended strategies.Through case studies that include the real experiences of Christian religion teachers, this article provides inspiring examples illustrating how Christian religion teachers have succeeded in filling the spiritual void of children from broken homes and achieving effective results. In the implications and recommendations section, the article highlights the important role of Christian religious teachers in filling the spiritual void of children from broken home families and emphasizes the need for collaboration between teachers, families and communities in supporting children's spiritual development. In conclusion, this article concludes that the role of Christian religious teachers is very important in filling the spiritual void of children from broken home families. With the right approach, Christian religion teachers can provide the spiritual support children need, assisting them in acquiring a sense of meaning, identity, and spiritual well-being. This article provides useful insights and insights for educators, parents, and practitioners in Christian religious education that aim to support the spiritual development of children from broken home families.